The Influence of Lewis Bond Media on Student Learning Outcomes of Chemical Bond Materials - Agus Kamaludin (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
The aim of the research is to find out  the influence of Lewis Bond media on student learning outcomes after participating in the learning process of chemical bonding materials. This research is a pre-experimental study with a one group pretest-posttest design. The sample of this research was 30 students of 10th grade of computer network engineering class II at SMK Muhammadiyah II Yogyakarta. The instrument of data collection was in the form of learning outcome test questions on chemical bonding materials. The data of student learning outcomes were analyzed by using paired sample t-test with SPSS 24.0. The analysis results obtained a sig value 0.05, which means that there is difference on student learning outcomes after using Lewis Bond media. It shows that the use of Lewis Bond learning media on chemical bonding materials is able to improve student learning outcomes.Keywords: Lewis Bond media, chemical bonds, learning outcomes